PENGARUH KELAS KEMIRINGAN DAN POSISI LERENG TERHADAP KANDUNGAN Fe TANAH SEBAGAI INDIKATOR KUALITAS LINGKUNGAN DAN KESUBURAN TANAH PADA ALFISOL DI DESA GUNUNGSARI KABUPATEN TASIKMALAYA - Fetty Dwi Rahmayanti (Agrisia: Jurnal Ilmu-Ilmu Pertanian, 2019)
This research was conducted to know the effect of slope class and slope position on Fe thickness. The study was using survey method and comparative descriptive analysis through physiographic approach freely based on physio-graphic land appearance. The sampling technique is based on the sampling me-thod of consideration in stratification. Soil samples were taken from three slope classes: 8-15%, 16-25% and 26-40% with three slope positions: top, middle and bottom positions. The results showed that the slope and slope position had an effect on the content of Fe. The highest content was on the slope of 16-25%. Based on the slope position, the highest Fe content was found in the downslope position. Soil foam can be used as an indicator of environmental quality and soil fertility. Keywords: Slope and Slope Position, Fe (iron), Environmental Quality, Soil Fer-tility.